Study of Immersion Behavior and Thermal Stability of Green Composite PLA/Bamboo - Komang Widhi Widantha; Risa Nurin Baiti; Made Widnya Kusuma (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
One way to address environmental problems caused by the use of synthetic materials is by exploring the potential of new materials that are more environmentally friendly. This research aims to develop PLA/bamboo green composites by investigating the effects of fiber composition and alkali treatment on the thermal stability and immersion behavior of the composites. PLA/bamboo composites were produced using the hot press method with bamboo fibers at 10, 20, and 30 wt.% concentrations. Alkaline treatment was conducted using a 5% NaOH concentration for 24 hours. The PLA/bamboo composite exhibited weight gain due to water absorption during the soaking process. The inclusion of bamboo composition increases the water absorption of the composite, whereas alkali treatment decreases the water absorption of the composite. Furthermore, the introduction of fibers also reduces the degradation temperature of the composite. This research is expected to provide valuable insights for the broader utilization of green composite materials.